Hubungan Hygiene Sanitasi dengan Kualitas Bakteriologis Depot Air Minum (DAM) di Kabupaten Balangan - Suriadi, Suriadi; Husaini, Husaini; Marlinae, Lenie (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Drinking water depo (DAM) continues to increase in line with the dynamics of the community needs to drinking water. DAM water contamination can be caused by  factor sanitation hygiene of the DAM. This research aims to determine of the relationshipbetweensanitary hygiene andbacteriological quality in the DAM. It is observational using cross sectional design. Thepopulation of this research was over all depo of drinking water in Balangan, while sample was takenby purposive sampling which has been determined based on inclusion and exclusion criteria. The research variables are location, building, production equipment, production process, sanitary facilities and bacteriological quality. The instrument used in this research was the observation sheets and laboratory tests. Data was analyzed by univariate, bivariate analysis using chi square test. The results showed from 41 DAM, there are 13 (31.7%)  less sanitary conditions of hygiene, 17 (41.5%) is enough and 11 (26.8%) good,  then  quality of bakteriologis are 30 (73%) eligible and 11 (27%)  not eligible. There is no relationship betwen locations (p = 0.698) and bacteriological quality, no relationship building (p=0.840) with the bacteriological quality, no relationship of production equipment (p=0.618) with the bacteriological quality, no relationship of production proces (p=0.986) with the bacteriological quality and there is no relationship of sanitation facilities (p=0.515) with bacteriological quality.The most of sanitation hygiene condition is notrelationshipto bacteriological quality of reffil drinking water depo.